Pendidikan Reproduksi (Seks) Pada Remaja; Perspektif Pendidikan Islam - Yadin Yadin (LP2M IAIN Palangka Raya, 2016)
As a belief system that emphasizes intregral living world and the hereafter, Islam also has the attention to the problem of reproductive (sex education). Sex education in Islam is not only intended for individuals who have already reached puberty but is also aimed at children from an early age. One of the important phases of age in human life is adolescence (puberty). Sex education to adolescents have urgency as education and anticipation of deviant behavior inflicted on the puberty. Islam underlines sex education as an integral part of education monoteism, worship and morality. This paper presents an overview of reproductive education in adolescents according to the perspective of Islamic education.